Comparative Efficacy and Safety of Standard Versus Accelerated Corneal Crosslinking for Keratoconus: 1-Year Outcomes From the Save Sight Keratoconus Registry Study. Issue 12 (20th December 2021) - Kandel, Himal; Nguyen, Vuong; Ferdi, Alex C.; Gupta, Aanchal; Abbondanza, Marco; Sullivan, Laurence; Apel, Andrew; Watson, Stephanie L.
Abstract : Purpose: The aim of this study was to compare the efficacy and safety of standard [Ultraviolet (UV) light power: 3 mW/cm 2, duration: 30 minutes] versus accelerated (UV power: 9 mW/cm 2, duration: 10 minutes) corneal crosslinking (CXL) for stabilizing keratoconus. Methods: A total of 684 eyes (555 patients; mean age ± SD, 25.0 ± 7.9 years; women, 30.6%) from 24 international sites with epithelium-off CXL for keratoconus had follow-up data at 1-year and met the inclusion criteria. Two hundred sixty-six eyes (228 patients) had undergone standard CXL, and 418 eyes (327 patients) had undergone accelerated CXL. The outcome measures included changes in visual acuity, keratometry, minimum corneal thickness, and frequency of adverse events. The outcomes were compared using mixed-effects regression models adjusted for age, sex, visual acuity, keratometry, pachymetry, doctor, practice, and eye laterality. Results: The adjusted mean changes (95% confidence interval) in outcomes were similar in standard and accelerated CXL in visual acuity [6.5 (2.0, 11.1) versus 5.5 (0.4, 10.6) logMAR letters, respectively], Kmax [−0.9 (−1.4, −0.3) D versus −1.2 (−1.9, −0.4) D, respectively], K2 [−0.4 (−0.9, 0.2) D versus −0.4 (−1.1, 0.3), D respectively], or minimum corneal thickness [−13.3 (−20.3, −6.3) μm versus −16.6 (−24.5, −8.6) μm, respectively] (all P > 0.05). The frequency of adverse events at the 12-month visit was also similar between the CXL groups (standard, 8.3% vs. accelerated, 5.5%; P = 0.21). Conclusions: This real-world observational study found that both standard and accelerated CXL were similarly safe and effective in stabilizing keratoconus at 1-year postsurgery in the real-world setting. The findings support the adoption of accelerated CXL for time and convenience.